Peran Yayasan Baitul MALLPLN dalam Meningkatkan Perekonomian Mustahiq dalam Penyaluran Dana Zakat - Muhammad Lutfhi Perdana Siregar; Andri Soemitra (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Distribution of zakat funds to develop the mustahiq economy is an act of charity in Islam where zakat funds are distributed to people who qualify as mustahiq (zakat recipients) with the aim of improving their welfare and economy. This process can be explained as, Mustahiq Identification The first step is to identify the person or family who qualifies as mustahiq. Mustahiq are individuals or families who meet the criteria of Islamic sharia and need financial assistance to meet their basic needs. Zakat Calculation Zakat is one of the religious obligations in Islam which orders Muslims to give a portion of their eligible assets to mustahiq. The distribution of zakat is based on calculating a certain percentage of assets subject to zakat. Distribution of Funds. After the zakat funds have been identified and calculated, the next step is to distribute the funds to the mustahiq. This can be done in various ways, including providing direct assistance, providing business capital, providing skills training, or providing interest-free loans.